Tribological and Structural Properties of Copper-Coated 3D-Printed Parts from Biodegradable Polymers - Mihaela Feraru (Ilie); Simona-Nicoleta Mazurchevici; Nicoleta-Monica Lohan; Marcelin Benchea; Fabian Cezar Lupu; Dumitru Nedelcu (Micromachines)
This manuscript highlights the behavior of biodegradable polymers (PLA and HD PLA Green) coated with two distinct bronze alloy powders, Metco 51F-NS (Cu 9.5Al 1.2Fe) and Metco 445 (Cu 9.5Al). The coating was realized on printed samples by using the Atmospheric Plasma Spray (APS) technique. The current investigation will explain the results related to the surface quality, micro-structure, morphology, and thermal and tribological properties. Thus, from a structural point of view, the most uniform deposition was obtained in the case of composite powder Metco 51F-NS. The thermal behavior of the samples coated with copper-based powder achieved stability up to temperatures slightly above 200 °C, with carbonization of the matrix structure taking place around 350 °C. The micro-indentation and scratch analysis responses were significantly influenced by the semicrystalline structure of the samples and the presence of the powder compounds. Based on the increased characteristics of the coated samples, the authors of the present paper consider that parts made of biodegradable polymers and coated with copper microparticles are appropriate for some applications which take place in adverse operating conditions.